IMPLEMENTASI PEMBELAJARAN INOVATIF-PROGRESIF DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Rusnawati (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This article aims to describe the fundamental concepts of innovative-progressive learning, its characteristics, the learning models associated with this approach, and its implications for instructional components. This study employed a qualitative library research method. Data were collected from relevant books, scientific journals, and other academic references and analyzed using a descriptive approach. The findings indicate that innovative-progressive learning encourages students to construct knowledge through direct experience, problem-solving activities, and the application of concepts to real-life situations. Its main characteristics include student-centered learning, the development of critical thinking, creativity, collaboration, and contextual learning. The approach can be implemented through various instructional models, including Direct Instruction, Contextual Teaching and Learning (CTL), Cooperative Learning, Quantum Learning, and Problem Solving. Furthermore, its implementation affects teachers' roles as facilitators, the development of instructional materials, the utilization of learning media, and the application of authentic assessment. Therefore, innovative-progressive learning is considered an effective approach to improving the quality of teaching and learning while fostering students' competencies to meet the demands of 21st-century education.